2001
DOI: 10.1067/mtc.2001.113025
|View full text |Cite
|
Sign up to set email alerts
|

Changes in aneurysm morphology and stent-graft configuration after endovascular repair of aneurysms of the descending thoracic aorta

Abstract: Excluded descending thoracic aortic aneurysms decrease in size on midterm follow-up. A subgroup of patients prone to neck dilatation might exist. A combination of neck dilatation and vector forces acting on stent-grafts in the tortuous thoracic aorta might lead to stent-graft migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 19 publications
0
47
0
2
Order By: Relevance
“…TAA endoleaks occur more commonly at the proximal or distal attachment sites (type I endoleak), whereas the majority of AAA endoleaks are type II. 94 It is generally accepted that type I endoleaks are more serious and require expeditious intervention because they represent direct communications between the aneurysm sac and aortic blood flow. 95 Treatment options include transcatheter coil or glue embolization, balloon angioplasty, placement of endovascular graft extensions, and open repair.…”
Section: Complicationsmentioning
confidence: 99%
“…TAA endoleaks occur more commonly at the proximal or distal attachment sites (type I endoleak), whereas the majority of AAA endoleaks are type II. 94 It is generally accepted that type I endoleaks are more serious and require expeditious intervention because they represent direct communications between the aneurysm sac and aortic blood flow. 95 Treatment options include transcatheter coil or glue embolization, balloon angioplasty, placement of endovascular graft extensions, and open repair.…”
Section: Complicationsmentioning
confidence: 99%
“…Since MDCTA is a very accurate imaging modality, an additionally performed calibrated intra-arterial DSA was not necessary. Concerning the morphologic changes of a thoracic aneurysm after successful endovascular exclusion, it has recently been demonstrated that excluded thoracic aortic aneurysms decrease in size similar to those found in abdominal aneurysms (approximately 10% yearly [6], 4 mm at 12-month follow-up) [21]. In our population we could demonstrate in 2 cases a decrease of aneurysm size of 4-5 mm after 1 year.…”
Section: Discussionmentioning
confidence: 57%
“…Our experimental testing proved that the anatomical stent significantly decreases the external strain force at both ends of the stent compare with that of the straight stent. By forming the Nitinol stent to match the expected change in aortic shape during the follow-up period [14][15][16], complications may be lessened as well.…”
Section: Discussionmentioning
confidence: 96%